El compromiso de adecuar la ley a un tratado: coalición o colisión (Tema Central) - Mogrovejo Jaramillo, Diego Fernando (2014)
Integration process comes from the premise of that a supranational obligation is assumed by the exercise of the State sovereignty; thus, it cannot be subject to inflictions. The dilemma emerges from this point: the national legislator, at the moment of adapting the law to the treaty, must apply the monist theory to connect the international system to the national one or apply the dualist theory to distinguish them. The Ecuadorian Constitution has tilted by the dualist system as soon as the international human rights treaties have been provided with constitutional status and the rest with legal status. As a result, the legislature must ensure that there is a correspondence between the contents of the law and the treaty, to first guarantee respect for the principles of pacta sunt servanda, legality and legal reserve in Criminal and Tax Law; and second, to ensure there is no collision between them.